Tingkat Altruisme Mahasiswa Bimbingan dan Konseling Universitas Negeri Semarang - Nusantara, Boby Ardhian; Hartati, Mt.Sri (Indonesian Journal of Guidance and Counseling: Theory and Application, 2013)
This research was carried out based on the phenomenon of lack of altruism and Guidance Department Student Counseling Semarang State University. The purpose of this research is to know the level of altruism majors guidance and counselling as well as knowing the difference of altruism and guidance counseling majors force by 2013, 2014 and 2015. This type of research is a research survey. The population of this research is a student guidance and Counselling Department State University of Semarang force by 2013, 2014 and 2015. Data collection techniques in the study using a scale of altruism with the amount of 85 grain statement has been tested previously. Analytical techniques descriptive analyses data using anova test and one way. The results showed that levels of altruism and guidance counselling students force by 2013, 2014 and 2015 has a percentage of the average number of 80.08%. The data are tested a Variant result fcount = 0.538 and ftable = 0.625 then fcount < ftable. so Ho accepted and Ha was rejected.